Scientific essays in honor of H. Pierre Noyes on the occasion of his 90th birthday - Kauffman, Louis H.; Amson, John C (Series on knots and everything, 2014)
This book celebrates the 90th birthday of physicist Pierre Noyes and features selected papers from the Alternative Natural Philosophy Association (ANPA). It explores topics central to ANPA's work, including the combinatorial hierarchy, discrete physics, and emergent quantum mechanics. The book also examines geometrical, cosmological, and biological aspects of these ideas. It is intended for readers interested in fundamental physics and innovative scientific perspectives.